2021
DOI: 10.1097/md.0000000000027203
|View full text |Cite
|
Sign up to set email alerts
|

Balanced crystalloids versus saline in critically ill patients

Abstract: Objective: To compare the safety of balanced crystalloids and saline among critically ill patients in intensive care unit (ICU). Methods: The Medline, EMBASE, Web of Science, Cochrane Library databases were systematically searched from the inception dates to May 17, 2020 in order to identify randomized controlled trials which evaluated the safety of balanced crystalloids and saline in critically ill patients. The primary outcome was major adverse kidney events within 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…However, by contrast, a recent meta-analysis involving 13 RCTs showed that balanced crystalloid solutions can reduce mortality in critically ill adults. Our analysis concluded that there was no evident difference in MAKE30 between these two groups, similar to previous studies [ 46 , 47 ]. It was detected that the balanced crystalloid solutions could not decrease the MAKE30 rate of ICU patients.…”
Section: Discussionsupporting
confidence: 91%
“…However, by contrast, a recent meta-analysis involving 13 RCTs showed that balanced crystalloid solutions can reduce mortality in critically ill adults. Our analysis concluded that there was no evident difference in MAKE30 between these two groups, similar to previous studies [ 46 , 47 ]. It was detected that the balanced crystalloid solutions could not decrease the MAKE30 rate of ICU patients.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to 0.9% sodium chloride, balanced electrolyte solutions comprise physiological or near-physiological concentrations of chloride and may therefore be advantageous [ 162 ]. Whereas a large RCT including 15,802 critically ill patients comparing balanced crystalloids versus 0.9% sodium chloride showed a lower rate of the composite outcome “death from any cause, new renal-replacement therapy or persistent renal dysfunction” when balanced crystalloids were used [ 163 ], one recently published RCT [ 164 ] and two meta-analyses comparing the effect of balanced crystalloids versus 0.9% saline for resuscitation of critically ill adults did not show a difference in mortality, acute kidney failure or length of hospital stay [ 165 , 166 ]. Nevertheless, knowing that further studies in trauma patients are warranted to clarify which crystalloid solution is the best for initial trauma management, the authors of this guideline favour a balanced electrolyte solution as the initial crystalloid solution in trauma patients.…”
Section: Resultsmentioning
confidence: 99%
“…Several meta-analyses have investigated the effect of BC vs. NS among critically ill patients [ 5 , 6 , 15 , 16 , 34 , 35 ]. Most meta-analyses showed no difference between BC and NS in mortality, the incidence of AKI, and the need for RRT among critically ill patients [ 5 , 15 , 16 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have investigated the effect of BC vs. NS among critically ill patients [ 5 , 6 , 15 , 16 , 34 , 35 ]. Most meta-analyses showed no difference between BC and NS in mortality, the incidence of AKI, and the need for RRT among critically ill patients [ 5 , 15 , 16 , 35 ]. Hammond et al [ 6 ] in 2020 demonstrated a lower mortality rate with BC than NS; however, no difference was observed in mortality on the subgroup of RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation